Vocabulario y estereotipos publicitarios en los anuncios de la prensa española actual - Głowicka, Monika (Studia Romanica Posnaniensia, 2007)
The author of this article analyses the functioning of stereotypes in Spanish press advertisements, payingspecial attention to the role which they play in this kind of texts. What is meant mainly is to show how advertisements try to modiify the consumer’s behaviour and to impose on him a new set of values which is in the interest of producers.